2008
DOI: 10.1007/s10404-008-0362-9
|View full text |Cite
|
Sign up to set email alerts
|

Computing flow, combustion, heat transfer and thrust in a micro-rocket via hierarchical problem decomposition

Abstract: This work describes the methodology developed to optimize the design of the combustion chamber, the thrust generating nozzle and the cooling system of a micro-rocket using numerical simulations. The coupling between combustion, subsonic/sonic/supersonic flow transition and heat transfer inside the micro-rocket is analysed using a problem decomposition strategy and state-of-the-art numerical techniques. First, the design of the thrust-generating nozzle is optimized, then, the mixing performances and the combust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Heat exchangers, combustion chambers, nuclear reactors and cooling systems in electronic devices are just some of the well-known examples in which significant temperature variations typically occur within the flow. Applications relevant for the present study can be found in aerospace systems, which operate in micro-gravity conditions and require liquidbased cooling technologies to meet high thermal transfer demand (Zonta, Marchioli & Soldati 2008;Campolo, Andreoli & Soldati 2009;Lee et al 2010). In these systems, thermal and viscous properties of the liquid are critical design parameters that vary with temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Heat exchangers, combustion chambers, nuclear reactors and cooling systems in electronic devices are just some of the well-known examples in which significant temperature variations typically occur within the flow. Applications relevant for the present study can be found in aerospace systems, which operate in micro-gravity conditions and require liquidbased cooling technologies to meet high thermal transfer demand (Zonta, Marchioli & Soldati 2008;Campolo, Andreoli & Soldati 2009;Lee et al 2010). In these systems, thermal and viscous properties of the liquid are critical design parameters that vary with temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we focus on the turbulence kinetic energy exchanges in strongly anisothermal wall-bounded flows at low Mach number. These flows are found in many industrial applications, including concentrated solar power plants [14,15,55,56,57,62], heat exchangers and cooling systems [73,10,35,74] or fluids at supercritical pressure within a small temperature range [68,52,47]. They are characterised by a strong influence on the energy exchanges of the walls and of temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade because of rapid advancement of various technologies, new approaches have been developed for applying classical combustion to novel fields such as microtechnology and nanotechnology. Many studies have been conducted to develop various microelectromechanical system‐based devices using combustion, including microthrusters, microreactors, micro­actuators, microrockets, and microengines . Most of these studies used a precisely designed microstructure to amplify the mechanical or thermal energies obtained from chemical combustion.…”
Section: Introductionmentioning
confidence: 99%